Pengaruh Edukasi Etika Batuk yang Benar Upaya Mencegah Penyakit TB Paru - Reisa Mardiana Putri; Lilis Llismayanti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Pulmonary tuberculosis remains the leading cause of death worldwide, and the spread of Mycobacterium tuberculosis through droplets is a major contributing factor. Education on proper cough etiquette is an important behavior-based prevention strategy to reduce the spread of this disease. This literature review aims to analyze the effect of cough etiquette education on preventing pulmonary TB transmission. This study used a literature search through Google Scholar and the Garuda portal for publications from 2020–2025, resulting in five articles meeting the inclusion criteria. The results indicate that cough etiquette education can improve public knowledge, skills, and awareness in preventing pulmonary TB transmission. This educational intervention has proven effective in various target groups, such as the general public, families of TB patients, and school-age children. In conclusion, cough etiquette education is an important component of pulmonary TB transmission prevention strategies and is highly feasible for widespread implementation in public health programs.